Minocycline promotes axonal regeneration through suppression of RGMa in rat MCAO/reperfusion model. Issue 4 (14th December 2012) - Tao, Tao; Xu, Guanghui; Si Chen, Cindy; Feng, Jinzhou; Kong, Yuhan; Qin, Xinyue
Abstract Minocycline has been recently implicated in protection against focal cerebral ischemia reperfusion (I/R), but the protective effects on neurobehavioral abnormalities remains contradictory. In the present study, we investigate whether minocycline improves axonal regeneration and neurological function recovery by inhibiting the expression of the repulsive guidance molecular A (RGMa) after focal cerebral ischemia reperfusion. Male Sprague‐Dawley (SD) rats were subjected to occlusion of the right middle cerebral artery (MCAO) for 2 h and 3 mg kg−1 minocycline was injected intravenously immediately after reperfusion twice a day for 14 days. The staircase test and modified neurological severity score (mNSS) were performed to evaluate functional outcome and blood‐brain barrier (BBB) permeability was assessed by Evan's blue dye extravasation (EB) at the expected time point. The expression of RGMa in ischemic cortex was measured by immunohistochemical staining and Western blot 2 weeks after MCAO. Neurofilament protein 200 (NF‐200) immunohistochemical staining was used to assess axonal damage. Treatment with minocycline at a dose of 3 mg kg−1 via the caudal vein significantly reduced the extravasation of EB, elevated mNSS and improved forelimb motor function as assessed by the staircase test when compared to the I/R group (P < 0.05). Moreover, axonal regrowth was enhanced in the minocycline treatment group when compared to the I/R group (P < 0.05). In addition, minocycline significantly reduced the expression of RGMa protein 2 weeks after MCAO as assessed by both immunostaining and Western blot. Our studies suggest that early minocycline treatment promotes neurological functional recovery and axonal regeneration in rats after MCAO, which might be mediated by down‐regulating RGMa expression. Synapse, 2013. © 2012 Wiley Periodicals, Inc.